On construction of rate-compatible low-density Parity-check codes - Yazdani, M.R.; Banihashemi, A.H. (IEEE communications letters, 2004)
In this letter, we present a framework for constructing rate-compatible low-density parity-check (LDPC) codes. The codes are linear-time encodable and are constructed from a mother code using puncturing and extending. Application of the proposed construction to a type-II hybrid automatic repeat request (ARQ) scheme with information block length k=1024 and code rates 8/19 to 8/10, using an optimized irregular mother code of rate 8/13, results in a throughput which is only about 0.7 dB away from Shannon limit. This outperforms existing similar schemes based on turbo codes and LDPC codes by up to 0.5 dB.